VAT Rate Increase and Regressivity: Evidence from Indonesia’s Consumption Tax Reform (Indonesian Tax Justice Review, 2024)
Value-added tax constitutes a central pillar of revenue mobilization in developing countries, yet its regressive effects raise persistent tax justice concerns. This paper analyzes Indonesia’s recent VAT rate increase and its distributional implications for different income groups. Using normative policy analysis supported by secondary empirical evidence, the study evaluates the extent to which compensatory social spending mitigates adverse welfare impacts. The findings demonstrate that although VAT reform strengthens fiscal capacity, existing compensation mechanisms only partially offset the burden borne by low-income households. The paper argues that reliance on consumption taxation without sufficient redistribution risks deepening inequality. The global contribution of this study lies in offering empirical insights from a large emerging economy undergoing consumption tax expansion. Indonesia’s experience provides comparative lessons for countries pursuing similar reforms under fiscal pressure, emphasizing the importance of integrating VAT policy with targeted redistribution. The paper contributes to global tax justice literature by reinforcing the argument that consumption tax reforms must be evaluated not only on efficiency grounds but also through equity-based frameworks that account for income distribution and social protection adequacy.